Comparison Between Algebraic Cryptanalysis on DES and NTRU - Paradise, Fadila; Sugeng, Kiki Ariyanti (InPrime: Indonesian Journal of Pure and Applied Mathematics, 2023)
AbstractAlgebraic cryptanalysis is a cryptanalysis method that aims to exploit the algebraic structure of an encryption algorithm to obtain the secret key. Algebraic cryptanalysis becomes interesting because it uses a small amount of known plaintext, which in real life very few known plaintexts are available. Algebraic cryptanalysis has previously been performed on several block cipher algorithms and public key lattice-based algorithms. In this study, DES and NTRU were chosen as the objects of algebraic cryptanalysis. This research aims to compare algebraic cryptanalysis on DES and NTRU in terms of their applicability, and to what extent algebraic cryptanalysis can be successful in obtaining keys.Keywords: Algebraic Cryptanalysis; DES; NTRU; polynomial equation. AbstrakAlgebraic cryptanalysis adalah metode kriptanalisis yang bertujuan untuk memanfaatkan struktur aljabar pada algoritma enkripsi untuk mendapatkan kunci. Algebraic cryptanalysis menarik karena hanya membutuhkan sedikit plaintext, di mana pada kehidupan nyata hanya sedikit plaintext yang bisa didapatkan. Algebraic cryptanalysis sebelumnya dilakukan pada algorima block cipher dan algoritma kunci publik berbasis latis. Pada penelitian ini, DES dan NTRU dipilih sebagai objek algebraic cryptanalysis. Penelitian ini bertujuan untuk membandingkan algebraic cryptanalysis pada DES dan NTRU, serta sejauh mana algebraic cryptanalysis bisa mendapatkan nilai kunci.Kata Kunci: Kriptanalisis aljabar; DES; NTRU; persamaan polinomial. 2020MSC: 94A60.